Chapter 10 Indigenous Networks and Evangelical Frontiers: Problems with Governance and Ethics in Cases of 'Voluntary Isolation' in Contemporary Amazonia - Brightman, Marc (Springer Nature, 2017)
The periodic emergence of indigenous peoples living in voluntary isolation in Amazonia have given rise to sensational media reports and heated academic debate. In this chapter we describe briefly the historical and contemporary relations between indigenous peoples in and out of isolation in the Guiana Shield region of North-eastern South America and discuss the role of indigenous missionaries in histories of contact. After considering these facts in relation to some of the general debates about isolated peoples and policy, we assess the ethical dimensions of the question of emergence from isolation.